Side Effects and Perceptions of COVID-19 Vaccination in Saudi Arabia: A Cross-Sectional Study - Al-Hanawi, Mohammed Khaled; Keetile, Mpho; Kadasah, Nasser Akeil; Alshareef, Noor; Qattan, Ameerah M. N.; Alsharqi, Omar (Frontiers in Medicine, 2022)
Vaccination against any disease condition is critical in improving and maintaining public health. However, the overall effectiveness of a vaccine largely depends on the willingness of a population to receive it. The main aim of this study was to assess the side effects and perceptions about COVID-19 vaccines among the adult population following vaccination in Saudi Arabia. An online cross-sectional survey was conducted from July 13 to July 20, 2021, among adults aged 18 years and older who had taken one or both doses of COVID-19 vaccines in Saudi Arabia. The survey included questions on socio-demographics, health behavior, vaccine type, knowledge about sources of information about COVID-19 vaccines, and perceptions and beliefs following vaccination. Bivariate and multivariable regression analyses were the major data analytic tools employed in the study. The most common vaccine side effects reported were tiredness/fatigue (52.6%), swelling (38%), fever (31.3%), headache (29.1%), and muscle pain (22.2%). In multivariable analyses, the odds of experiencing severe side effects were significantly higher among males [adjusted odds ratio (aOR) = 2.76, 95% confidence interval (CI) = 1.71–4.45, p < 0.01), those aged 40–49 years (aOR = 3.10, 95% CI = 1.10–8.72, p < 0.1), and Saudi nationals (aOR = 3.64, 95% CI = 1.58–8.38, p < 0.05) compared to their counterparts. The odds of believing that COVID-19 vaccines are safe in the long-term were significantly higher among men (aOR = 1.76, 95% CI = 1.16–2.65, p < 0.01) and among individuals who had received two doses (aOR = 1.62, 95% CI = 1.09–2.40, p < 0.05), and the odds of advising others to get vaccinated for COVID-19 were also significantly higher among respondents who had received two doses (aOR = 2.81, 95% CI = 1.60–4.93, p < 0.01) compared to their counterparts. This study identified the most common COVID-19 vaccine side effects in Saudi Arabia, therefore making them predictable. This information will help reduce vaccine hesitancy as booster doses become available.